Assessment of EnMAP data quality through global product validation activities - Maximilian Brell; Philipp Reiners; Luis Guanter; Karl Segl; Sabine Chabrillat; Daniel Scheffler; Mariana A. Soppa; Niklas Bohn; Javier Gorrono; Alexander Kokhanovsky; Astrid Bracher; Martin Bachmann; et al. (Remote Sensing of Environment, 2026)

Chronology of recent sedimentary infill of the Inner Río de la Plata Estuary, Argentina - Ferran Colombo; Jordi Serra; Patricia Cabello; José Bedmar; Federico I. Isla (Journal of Iberian Geology, 2021)
The Inner Río de la Plata Estuary is a sedimentary depositional system that resulted from fluvial-deltaic activity. Gentle Pliocene–Pleistocene slopes make-up the northern side of the estuary whereas small cliffs of the same age constitute the southern side. A long coastal estuarine barrier developed at about 6000 years BP when the maximum flooding surface occurred. Attached to this barrier, and at a lower elevation, is a large strandplain (covering an area of about 2400 km 2 ) which displays more than 220 beach ridges. In different areas, the dating indicates a periodicity of 13.4–13.7 years for the development of each beach ridge. These data are like the periodicity of the ENSO effects, which could be associated with the variability of Sunspots. These ridges were formed shortly after the maximum flooding surface, which was followed by a gradual fall in sea-level that contributed significantly to the Inner Río de la Plata Estuary sedimentary infill. In addition, ENSO activities were probably instrumental in the distribution of the main geoforms in the Inner Rio de la Plata Estuary. Small deltas, which were generated by other rivers and creeks such as the Nogoyá Arroyo and the Gualeguay River, developed coevally with the coastal estuarine barrier. The Ibicuy Delta grew in the middle of the inner Río de la Plata Estuary when the former Paraná River flowed northwards during the sea-level fall. The upper part of the delta front was reworked, giving rise to a large dunefield. Thereafter, a chenier plain developed along with tidal flats. The current Paraná Delta continues to prograde at a rate of about 56–64 m/year (m year −1 ). The sedimentary infill of the Inner Río de la Plata Estuary occurred along the Holocene.

Quaternary over-elevated torrential channels. Characteristics and depositional significance: the Maresme model (Catalonia, NE Spain) - Ferran Colombo; Lluis Rivero (International Journal of Earth Sciences, 2017)